2015
DOI: 10.1152/ajplung.00333.2015
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of soluble guanylate cyclase modulators in neonatal chronic lung disease

Abstract: Wagenaar GT, Hiemstra PS, Gosens R. Therapeutic potential of soluble guanylate cyclase modulators in neonatal chronic lung disease. Am J Physiol Lung Cell Mol Physiol 309: L1037-L1040, 2015. First published October 2, 2015; doi:10.1152/ajplung.00333.2015.-Supplemental oxygen after premature birth results in aberrant airway, alveolar, and pulmonary vascular development with an increased risk for bronchopulmonary dysplasia, and development of wheeze and asthma, pulmonary hypertension, and chronic obstructive pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…Chronic asthma is an inflammatory airway disorder characterized by AHR and airway remodeling ( Lim et al, 2017 ). Increased mucous gland hyperplasia, extracellular matrix deposition, and the proliferation of airway SMC may result in lung function decline ( Wagenaar et al, 2015 ). Increased bulk of HBSM plays an important role in airway remodeling derived from subjects with asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic asthma is an inflammatory airway disorder characterized by AHR and airway remodeling ( Lim et al, 2017 ). Increased mucous gland hyperplasia, extracellular matrix deposition, and the proliferation of airway SMC may result in lung function decline ( Wagenaar et al, 2015 ). Increased bulk of HBSM plays an important role in airway remodeling derived from subjects with asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, the beneficial effect on vascular remodeling can also be mediated via ibuprofen's offtarget effect of elevating intracellular cGMP levels via cGMP-selective phosphodiesterase (PDE) inhibition [54,55]. This explanation is supported by the beneficial effects of agents that increase intracellular cGMP levels, either by stimulating the NO-eNOS-cGMP pathway with inhaled NO, apelin or soluble guanylate cyclase modulators or inhibiting cGMP breakdown with the specific cGMP-selective PDE5 inhibitor sildenafil, in newborn rats with experimental BPD that our group and others described previously [9,50,[56][57][58]. Interestingly, the beneficial effects of ibuprofen on experimental BPD may be explained by activation of the apelin/APJ pathway, which we have demonstrated to protect against experimental BPD in rats [9].…”
Section: Discussionmentioning
confidence: 83%
“…This study provides the first evidence that Ca 2+ signaling is modified in PASMC from newborn rat with BPD-PH. Interestingly, Ca 2+ signaling in PASMC plays a central role both in vasoconstriction, through its pivotal effect on PASMC contraction, and in vascular remodeling, through its stimulatory effect on PASMC proliferation and migration [ 32 , 33 ]. We demonstrated that the resting [Ca 2+ ] cyt is higher in the PASMC from hyperoxic newborn rats than in those from controls.…”
Section: Discussionmentioning
confidence: 99%